2001
DOI: 10.1128/mcb.21.17.5733-5741.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Fungal MEP Proteins Mediate Diffusion of the Uncharged Species NH3 across the Cytoplasmic Membrane

Abstract: Methylammonium and ammonium (MEP) permeases of Saccharomyces cerevisiae belong to a ubiquitous family of cytoplasmic membrane proteins that transport only ammonium (NH 4 ؉ ؉ NH 3 ). Transport and accumulation of the ammonium analog [14 C]methylammonium, a weak base, led to the proposal that members of this family were capable of energy-dependent concentration of the ammonium ion, NH 4 ؉ . In bacteria, however, ATP-dependent conversion of methylammonium to ␥-N-methylglutamine by glutamine synthetase precludes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 69 publications
6
73
2
Order By: Relevance
“…Our results support previous speculation (17) that Rh proteins may facilitate diffusion of NH 3 . However, it was also proposed recently that the Rh1 protein paralog of the green alga Chla- mydomonas reinhardtii might be regarded as a gas channel for CO 2 , because mutants lacking this protein grow only very slowly when cultured in high CO 2 conditions (48).…”
Section: Ch3nh2͞nh3 Transport Function Is Mediated By a Protein-depensupporting
confidence: 83%
See 1 more Smart Citation
“…Our results support previous speculation (17) that Rh proteins may facilitate diffusion of NH 3 . However, it was also proposed recently that the Rh1 protein paralog of the green alga Chla- mydomonas reinhardtii might be regarded as a gas channel for CO 2 , because mutants lacking this protein grow only very slowly when cultured in high CO 2 conditions (48).…”
Section: Ch3nh2͞nh3 Transport Function Is Mediated By a Protein-depensupporting
confidence: 83%
“…Some studies suggested that RhAG-mediated uptake of MA in oocytes was an electroneutral NH 4 ϩ ͞H ϩ exchange (13), whereas electrophysiological studies in voltage-clamped RhBG-and RhCGexpressing oocytes suggested that transport is (14,15) or is not (16) electrogenic. It was also speculated that Rh and Mep͞Amt proteins might be facilitators for NH 3 gas transport (17).…”
mentioning
confidence: 99%
“…Although inconsistent, all of the studies cited above concluded that Rh proteins, like their only known paralogues, the ammonium͞methylammonium transport (Amt) proteins [also called methylammonium permeases (Mep) in Saccharomyces cerevisiae], were active transport systems for the ion NH 4 ϩ . Disruption of an Rh gene in the slime mold Dictyostelium discoideum yielded no phenotype (16).Contrary to views of others, we have proposed that Amt͞Mep proteins are bidirectional channels for the uncharged species NH 3 and constitute an example of biological gas channels (12,(17)(18)(19)(20). There is now considerable genetic and physiological evidence to support this view in several microorganisms.…”
mentioning
confidence: 56%
“…In contrast to the prevailing view of interpreting cellular methylammonium accumulation as Amt/MEP-mediated secondary transport as reviewed by von Wire´n and Merrick [42], Kustu and collaborators [37,39,40] have attributed this accumulation to metabolic trapping by glutamine synthetase or to trapping in acidic vacuoles in the case of fungi. They proposed instead that Amt/MEP proteins simply mediate bi-directional NH 3 transport and this view is now strongly supported by the structural results.…”
Section: Amt /Mep-mediated Ammonia Uptake For Nutritionmentioning
confidence: 70%